A computational pipeline for sepsis patients’ stratification and diagnosis - Campos, David; Pinho, Renato; Neugebauer, Ute; Popp, Juergen; Oliveira, José Luís (HEALTHINF 2018 - 11th International Conference on Health Informatics, Proceedings; Part of 11th International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2018, 2018)
Sepsis is still a little acknowledged public health issue, despite its increasing incidence and the growing mortality rate. In addition, a clear diagnosis can be lengthy and complicated, due to highly variable symptoms and non-specific criteria, causing the disease to be diagnosed and treated too late. This paper presents the HemoSpec platform, a decision support system which, by collecting and automatically processing data from several acquisition devices, can help in the early diagnosis of sepsis.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Blood Testing; Data Analysis; Early Diagnosis; Sepsis; Septic Shock